SMOKING IN THE FAMILY AND THE INCIDENCE OF RESPIRATORY INFECTIONS IN TODDLERS - Hartawan (Yayasan Pendidikan Medika Indonesia, 2025)
Respiratory tract infections (RTIs) are one of the most serious respiratory diseases and cause the highest number of deaths. To date, RTIs remain a global health issue. Deaths from respiratory infections among infants reach 12.4 million annually worldwide among children aged 0–4 years, with two-thirds of these being infants aged 0–1 years, and 80.3% of these deaths occurring in developing countries. Factors that may influence the incidence of ARI include parental smoking, with the harmful effects of secondhand smoke being greater for passive smokers than active smokers, population density, and low birth weight (LBW). Tobacco smoking, as one of the causes of ISPA, is the third leading cause of death after coronary heart disease and cancer. Exposure to tobacco smoke affects the incidence of ISPA in infants, with infants exposed to tobacco smoke being at a higher risk of developing ISPA compared to those not exposed to tobacco smoke.